2002
DOI: 10.1046/j.1365-2672.2002.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of solar inactivation of Escherichia coli by titanium dioxide photocatalytic oxidation

Abstract: Aims: To improve solar water disinfection using a photocatalysing semi-conductor and to study the mechanisms involved in this process. Methods and Results: Cells of Escherichia coli were used as the microbiological indicator to study the possibility of improving the efficiency of solar water disinfection using titanium dioxide (TiO 2 ) as a photooxidizing semi-conductor. TiO 2 was used either as a suspended powder or in an immobilized form. Both applications improved the efficiency of solar disinfection. TiO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 31 publications
(45 reference statements)
0
47
0
3
Order By: Relevance
“…Malondialdehyde (MDA) is released as a product of membrane degradation. It has been suggested that the free radicals •OH and H 2 O 2 were responsible for killing close to the TiO 2 , with H 2 O 2 acting at a distance (118,(148)(149)(150)(151)(152). Direct oxidation of bacterial components is feasible when cells are in direct contact with the surface of TiO 2 .…”
Section: In Vitro Evaluation Of Tio 2 Antibacte-rial Activitymentioning
confidence: 99%
“…Malondialdehyde (MDA) is released as a product of membrane degradation. It has been suggested that the free radicals •OH and H 2 O 2 were responsible for killing close to the TiO 2 , with H 2 O 2 acting at a distance (118,(148)(149)(150)(151)(152). Direct oxidation of bacterial components is feasible when cells are in direct contact with the surface of TiO 2 .…”
Section: In Vitro Evaluation Of Tio 2 Antibacte-rial Activitymentioning
confidence: 99%
“…Sunlight exposure combined with water temperatures of 45-508C resulted in rapid, synergistic inactivation, (Wegelin et al 1994;Sommer et al 1997;McGuigan et al 1998) leading to the use of reflectors (Kehoe et al 2001;Rijal & Fujioka 2003;Mani et al 2006), bottles with the bottoms painted black (Sommer et al 1997), and thermoregulated reactors (Sommer et al 1997) to accelerate the process. Several groups have used TiO 2 as a suspended catalyst or coated onto a support to accelerate the photoinactivation of bacteria, (Ireland et al 1993;Dunlop et al 2002;Salih 2002;Rincon & Pulgarin 2004, 2006 while others have proposed the use of photosensitizers such as methylene blue in SODIS (Acher & Juven 1977;Wegelin et al 1994). These modifications have proven effective and promising, but still pose problems.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effects of TiO 2 , either in suspension or immobilized, have been studied with respect to substrate support (e.g., glass and stainless steel) (2,12,25,37), the Ag/TiO 2 molar ratio (37), and the light source and wavelength (13,17,21,27). However, bactericidal effects are also affected by the condition of the glass coating, the photocatalyst ratio, and the sterilization process.…”
mentioning
confidence: 99%